2021
DOI: 10.3389/fphar.2021.641917
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Alleviates Methamphetamine-Induced Hepatotoxicity by Suppressing the p53 Pathway-Mediated Apoptosis, Autophagy, and Inflammation in Rats

Abstract: Misuse of the psychostimulant methamphetamine (METH) could induce serious hepatotoxicity. Our previous study revealed the effects of luteolin on alleviating METH-induced hepatotoxicity, however, the detailed mechanisms have not been elucidated. In this study, rats were orally pretreated with 100 mg/kg luteolin or sodium dodecyl sulfate water, and then METH (15 mg/kg, intraperitoneal [i.p.]) or saline was administered. Histopathological and biochemical analyses were used to determine the alleviative effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…It has been confirmed that METH induces hepatotoxicity in humans, rats, and cells ( Dias Da Silva et al, 2013 ; Zhao et al, 2020 ; Zhang et al, 2021 ). Consistent with findings, this research demonstrated that the escalating dose/multiple binge METH model could also lead to hepatotoxicity in mice, indicated by histopathological examination and ALT and AST activities.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It has been confirmed that METH induces hepatotoxicity in humans, rats, and cells ( Dias Da Silva et al, 2013 ; Zhao et al, 2020 ; Zhang et al, 2021 ). Consistent with findings, this research demonstrated that the escalating dose/multiple binge METH model could also lead to hepatotoxicity in mice, indicated by histopathological examination and ALT and AST activities.…”
Section: Discussionmentioning
confidence: 88%
“…However, preconditioning of chlorogenic and caftaric acids could prevent liver toxicity and oxidative stress induced by METH injections ( Koriem and Soliman, 2014 ). Similarly, our team demonstrated that METH induced hepatotoxicity by inducing cell cycle arrest and activating apoptosis ( Wang et al, 2017 ) and luteolin exerted protective effects against METH hepatotoxicity by suppressing apoptosis, autophagy, and inflammation in rats ( Qu et al, 2020 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 84%
“…A western blot assay was performed to investigate neurotoxicity and colonic toxicity associated with MA. The RIPA lysis method was used to isolate total proteins of striatum and colonic mucosa as previously described ( Zhang et al, 2021 ). The primary antibodies used were: anti-monoamine oxidase A (MAOA; 1:1,000, 4A Biotech, Cat# 4ab091383), anti-dopamine transporter (DAT; 1:1,000, Bioss, Cat# bs-1714R), anti-tyrosine hydroxylase (TH; 1:1,000, Proteintech, Cat# 25859-1-AP), anti-caspase 3 (1:1,000, ABclonal, Cat# A2156), anti-cleaved caspase 3 (1:1,000, CST, Cat# 9661), anti-p53 (1:1,000; 4A Biotech, Cat# 4ab087781), anti-Bax (1:1,000, CST, Cat# 2772), anti-Beclin 1 (1:1,000, CST, Cat# 3738), anti-LC3-II (1:1,000; Proteintech, Cat# 18725-1-AP), anti-autophagy-related 5 (Atg5; 1:1,000; HuaAn Biotechnology, Cat# ET1611-38), anti-Claudin-5 (1:1,000, Abclonal, Cat# A10207), anti-Occludin (1:1,000, Abclonal, Cat# A2601), anti-TLR4 (1:1,000, SANTA, Cat# sc-293072), anti-MyD88 (1:1,000, CST, Cat# 4283S), anti-NF-κB (1:1,000, Proteintech, Cat# 10745-1-AP), anti-NLRP3 (1:1,000, Abcam, Cat# ab263899), anti-IL-6 (1:1,000, 4A Biotech, Cat# 4ab044340), anti-IL-18 (1:1,000, Proteintech, Cat# 60070-1-lg), anti-TNF-α (1:1,000, 4A Biotech, Cat# 17590-1-AP), anti-caspase 1 (1:1,000, Proteintech, Cat# 22915-1-AP), and anti-β-actin (1:1,000; 4A Biotech, Cat# 4ab071291).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, METH treatment impairs liver metabolism by disrupting the CYP1A2 metabolic pathway [ 7 ]. It also induces hepatotoxicity by arresting the cell cycle, inhibiting cell division, and activating apoptosis and autophagy [ 5 , 8 ]. The promotion of apoptosis restricts inflammation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%